DINAMIC OF BIOENERGETIC POTENTIAL OF SOIL IN VOJVODINA - Jan, Marko; Jovanović, Milenko; Nikolić-Đorić, Emilija; Marković, Todor (Economics of Agriculture, 2011)
Bioenergetic potential of the soil (expressed as total dry matter produced) does not use the same intensity. In certain periods exercised proper growth of production, while the other observes at first fatigue, then its often pronounced decline and finally a slight increase. The paper concludes dependence between the quantity of all forms of active substances (N, P2O5, K2O) that is stored in the soil and the volume of produced organic mass expressed as absolute dry substance. Is an open question whether the production could increase in the coming period to a level that is accomplished by three decades ago